Identification and expression analysis of zebrafish gnaq in the hypothalamic–Pituitary–Gonadal axis - Wang, Chong; Yang, Le; Xiao, Tiaoyi; Li, Junhua; Liu, Qiaolin; Xiong, Shuting (Frontiers in Genetics, 2022)
The G proteins have emerged as essential molecular switches in a wide variety of signal transduction pathways. Gαq, encoded by G proteins subunit alpha q (gnaq), is a member of G proteins and participates in regulating important biological activities in mammals, while its function and regulatory mechanism in teleost remain largely unclear. In the current study, we cloned the cDNA of gnaq from zebrafish (Danio rerio) and investigated the expression characteristics of Gαq/gnaq in reproductive tissues. RT-PCR and WISH analyses showed that the gnaq was widely expressed in zebrafish tissues, with high expression in the brain, olfactory brain, and hypothalamus. During the embryonic development stage, the gnaq was mainly distributed in the hypothalamus after 72 hours post-fertilization. Besides, immunohistochemistry analysis showed that the Gαq protein was highly expressed in the diffuse nucleus of the inferior hypothalamic lobe (DIL), ventral zone of the periventricular hypothalamus (Hv), and caudal zone of periventricular hypothalamus (Hc) in adult zebrafish. Furthermore, in gonads, the Gαq protein was found in oocytes of all stages and testis except spermatids. Lastly, the gnaq mRNA exhibited a relatively low expression level in gonads on day 4 during a reproductive cycle, while increasing drastically in the hypothalamus and pituitary afterward. Altogether, our results suggest that gnaq/Gαq might play important roles in fish reproduction.